2017
DOI: 10.1038/jhg.2017.84
|View full text |Cite
|
Sign up to set email alerts
|

Precise mapping of 17 deletion breakpoints within the central hotspot deletion region (introns 50 and 51) of the DMD gene

Abstract: Exon deletions in the human DMD gene, which encodes the dystrophin protein, are the molecular defect in 50-70% of cases of Duchenne/Becker muscular dystrophies. Deletions are preferentially clustered in the 5' (exons 2-20) and the central (exons 45-53) region of DMD, likely because local DNA structure predisposes to specific breakage or recombination events. Notably, innovative therapeutic strategies may rescue dystrophin function by homology-based specific targeting of sequences within the central DMD hot spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…The reason for the high rate of deletion and low rate of small mutation might be that the patients enrolled in our hospital were mainly deletions and duplications. In addition, we found that deletions preferentially clustered in one hot-spot region that located between exon 43-55 of DMD gene which was in agreement with previous studies in other populations [22,23]. Likewise, two hot spot regions were located for duplications, which were exon 8-11 and exon 51.…”
Section: Discussionsupporting
confidence: 92%
“…The reason for the high rate of deletion and low rate of small mutation might be that the patients enrolled in our hospital were mainly deletions and duplications. In addition, we found that deletions preferentially clustered in one hot-spot region that located between exon 43-55 of DMD gene which was in agreement with previous studies in other populations [22,23]. Likewise, two hot spot regions were located for duplications, which were exon 8-11 and exon 51.…”
Section: Discussionsupporting
confidence: 92%
“…This is also an interesting finding since mechanisms underlining deletion and duplication events are different indeed. Deletions seem to be frequently related to micro-homology in breakpoint regions, mainly due to the presence of short tandem repeats, interspersed repeat elements which can predispose to deletion events (Esposito et al, 2017) or (as already mentioned above) due to an aberrant firing replication fork. Duplications are known to arise from either homologous (such as Alu-Alu) recombination or nonhomologous recombination, which is mediated by topoisomerases activity.…”
Section: Dmd Deletions and Duplications: Frequency Distribution Topmentioning
confidence: 97%
“…Effective treatments are limited for DMD patients, and research for genetic-based therapies is ongoing [7]. As a consequence, the analysis of the DMD gene is of utmost importance for the identification of the underlying molecular defect, because it can confirm the clinical diagnosis, reveal patients' genotype, address patients to the most opportune therapeutic options, and allow the identification of carrier females and the application of prenatal tests [8][9][10].…”
Section: Introductionmentioning
confidence: 99%